Pengaruh Model Pendidikan Olahraga terhadap Kecerdasan Interpersonal Siswa Sekolah Dasar dalam Pembelajaran Bola Voli - Faiz Faozi; Debi Krisna Irawan; Sri Sundari; Alifudien Putra Setia; Syamsul Bahri (Indonesian Journal of Physical Education and Sport Science, 2026)
Study purpose. Contemporary education emphasizes holistic student development, including social and emotional competencies such as interpersonal intelligence. However, research on integrating Social and Emotional Learning (SEL) into physical education through structured pedagogical models remains limited, particularly in non-Western educational contexts like Indonesia. Objectives: This study aims to analyze the effect of implementing the Sport Education Model (SEM) on enhancing the interpersonal intelligence of elementary school students within volleyball instruction.  Materials and methods. A true experimental design with a pretest-posttest control group structure was employed. The sample consisted of 64 fifth-grade students from SDN Cidadap 3, divided into an experimental group (n=32) taught using SEM and a control group (n=32) taught using conventional direct instruction. Data were collected using a validated interpersonal intelligence questionnaire and analyzed statistically using paired sample t-tests.  Results. The results indicated that both groups showed significant improvement in interpersonal intelligence scores. However, the improvement in the experimental group (+16 points) was substantially greater than that in the control group (+4 points).  Conclusions. These findings suggest that SEM is significantly more effective in developing students' interpersonal competencies such as empathy, communication, cooperation, and social skills compared to the conventional approach. Implications: Theoretically, this study contributes to the literature on pedagogical models in physical education by demonstrating SEM's potential as a framework for integrating SEL into sport instruction. Practically, the findings encourage physical education teachers to adopt SEM to foster students' interpersonal intelligence, particularly in elementary school settings where social-emotional development is critical. Policymakers and curriculum developers should consider supporting SEM implementation through professional development and resources to maximize physical education's role in holistic student development.